Somatic and germline FOXP3 mosaicism in the mother of a boy with IPEX syndrome. Issue 5 (23rd February 2018) - Lin, Yunting; Xu, Aijing; Zeng, Chunhua; Cheng, Jing; Li, Na; Niu, Huilin; Liu, Li; Li, Xiuzhen
Abstract : Confirmatory Sanger sequencing of whole exome sequencing first identified a somatic and germline FOXP3 mosaicism with two different mutational events of c.210 + 1G > T and c.210 + 1G > A in the mother of a boy with IPEX syndrome.